Natural Film-Forming Polymers for Antibacterial Mucoadhesive Oral Films Against Streptococcus mutans Biofilms in Dental Caries Prevention: A Narrative Review - Elrey Naufal Hidayat; Ghani Phalosa (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Dental caries remains a persistent oral health problem because cariogenic biofilms, particularly those involving Streptococcus mutans, can adhere to dental surfaces, produce extracellular polysaccharides, generate acids, and promote enamel demineralization. Conventional preventive approaches often face limitations in the oral cavity due to salivary flow, swallowing, short contact time, and reduced local retention of antibacterial agents. This narrative review evaluates natural film-forming polymers as antibacterial mucoadhesive oral films for controlling Streptococcus mutans biofilms and proposes a function-based framework to guide polymer selection for dental caries prevention. The review focuses on chitosan, alginate, pectin, pullulan, gelatin, starch, and natural gums by analyzing their film-forming capacity, mucoadhesive behavior, mechanical properties, controlled-release performance, and antibacterial relevance. Chitosan shows the strongest functional potential because it combines film formation, mucosal adhesion, and intrinsic antibacterial and antibiofilm activity. Alginate and pectin mainly support swelling, gel formation, and sustained release, while pullulan improves film transparency, flexibility, disintegration behavior, and patient acceptability. Gelatin, starch, and natural gums provide additional structural and adhesive benefits, although they often require plasticizers, blending, or modification to improve stability and mechanical strength. Current evidence suggests that rational polymer blending, especially chitosan-based composite systems, offers the most feasible strategy for developing effective antibacterial oral films. However, most available studies remain limited to in vitro formulation and antibiofilm evaluations. Future research should prioritize standardized comparative testing, multispecies biofilm models, clinical validation, residence-time assessment, sensory acceptability, and long-term caries-preventive outcomes.